2021
DOI: 10.1002/ajmg.c.31959
|View full text |Cite
|
Sign up to set email alerts
|

Urogynaecology and Ehlers–Danlos syndrome

Abstract: Ehlers-Danlos syndrome (EDS) can lead to a presentation to urogynaecology services with multiple symptoms including vaginal prolapse, overactive bladder symptoms, voiding dysfunction, bladder pain syndrome, recurrent urinary tracts infections, stress urinary incontinence, recurring bladder diverticula, vesicoureteral reflux, pelvic floor pain or spasms, and complicated postnatal perineal wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…It has also been reported that the volume of residual urine after voiding may be 100-200 mL in EDS patients. 2 This finding is thought to be due to non-neurogenic bladder Fig. 3 Image of the renal pelvis mucosa after calculus crushing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that the volume of residual urine after voiding may be 100-200 mL in EDS patients. 2 This finding is thought to be due to non-neurogenic bladder Fig. 3 Image of the renal pelvis mucosa after calculus crushing.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for postoperative urinary tract infections following TUL include operative time, preoperative pyuria, and preoperative CT findings. [8][9][10] Patients with EDS are at high risk of developing urinary tract infections, 2 and pyuria suggests a relatively high risk of postoperative infections following upper urinary tract procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of urinary incontinence in women with EDS is reported to be between 69% and 84%, compared to 30% in the general population, with a higher risk of incontinence and prolapse after childbirth [20]. Urological symptoms can be due to connective tissue and pelvic floor muscle defect [41], which results in insufficient bladder support [40].…”
Section: Gastrointestinal Symptomsmentioning
confidence: 99%